2012
DOI: 10.1002/lary.23179
|View full text |Cite
|
Sign up to set email alerts
|

A functional variation in the hypocretin neuropeptide precursor gene may be associated with obstructive sleep apnea syndrome in Japan

Abstract: Our genetic association study, followed by functional and quantitative phenotyping assays, demonstrated a functional locus within the HCRT gene, which may act to increase HCRT expression and lead to a protective effect against the development of OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Abnormalities in orexin signaling pathways underlie the pathophysiology of sleep disorders (Baumann and Bassetti, 2005a, b; Cao and Guilleminault, 2011; Dyken and Yamada, 2005; Malhotra and Kushida, 2013; Mignot, 2004; Overeem et al, 2001; Ritchie et al, 2010; Tafti et al, 2005; Taheri et al, 2002; Wisor and Kilduff, 2005; Zeitzer, 2013) such as narcolepsy (Nishino et al, 2000; Peyron et al, 2000; Thannickal et al, 2000) and may contribute to posttraumatic hypersomnia or excessive daytime sleepiness due to traumatic brain injury (Baumann, 2012; Baumann et al, 2009), post traumatic stress disorder (Strawn et al, 2010), or obstructive sleep apnea (Ahmed et al, 2012; Wang et al, 2013). Insufficient central orexin signaling has also been associated with other medical conditions (Mignot et al, 2002; Vankova et al, 2003) such as obesity (Van Cauter and Knutson, 2008), age-related anorexia (Kmiec et al, 2013), multiple system atrophy (Benarroch et al, 2007), neurological disorders (Fronczek et al, 2009), Parkinson’s disease (Fronczek et al, 2007; Thannickal et al, 2007; Wienecke et al, 2012), and Alzheimer’s disease (Slats et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in orexin signaling pathways underlie the pathophysiology of sleep disorders (Baumann and Bassetti, 2005a, b; Cao and Guilleminault, 2011; Dyken and Yamada, 2005; Malhotra and Kushida, 2013; Mignot, 2004; Overeem et al, 2001; Ritchie et al, 2010; Tafti et al, 2005; Taheri et al, 2002; Wisor and Kilduff, 2005; Zeitzer, 2013) such as narcolepsy (Nishino et al, 2000; Peyron et al, 2000; Thannickal et al, 2000) and may contribute to posttraumatic hypersomnia or excessive daytime sleepiness due to traumatic brain injury (Baumann, 2012; Baumann et al, 2009), post traumatic stress disorder (Strawn et al, 2010), or obstructive sleep apnea (Ahmed et al, 2012; Wang et al, 2013). Insufficient central orexin signaling has also been associated with other medical conditions (Mignot et al, 2002; Vankova et al, 2003) such as obesity (Van Cauter and Knutson, 2008), age-related anorexia (Kmiec et al, 2013), multiple system atrophy (Benarroch et al, 2007), neurological disorders (Fronczek et al, 2009), Parkinson’s disease (Fronczek et al, 2007; Thannickal et al, 2007; Wienecke et al, 2012), and Alzheimer’s disease (Slats et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, it seems reasonable to speculate that HCRT variants are not involved in the development of OSAHS. The previous study reported that circulating hypocretin levels were significantly lower in OSAHS patients than controls, and inversely correlated with the severity of OSAHS [ 19 , 20 ]; however, a clinical trial by Ahmed et al [ 8 ] had previously found that the frequency of the HCRT rs9902709 variation increased HCRT expression, and was associated with a decreased risk for OSAHS in the Japanese population. These differences between the two studies may be primarily attributed to environmental factors which have the potential to interact with the genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…An association between Ala20Val polymorphism and C/C variant of the GABBR1 Phe658Phe polymorphism and OSAHS had been reported in Turkish individuals [ 6 ], but not for the genotype and allele frequencies of IRS-1 rs1801278 [ 7 ]. In addition, also, an association between the C allele of the HCRT rs9902709 variation and OSAHS was reported in a Japanese population [ 8 ]. Hence based on these findings the objective of this study was to investigate genotype-phenotype changes between rs29230 in γ-aminobutyric acid B receptor (GABBR1) , rs1801278 in insulin receptor substrate-1 (IRS-1) , rs9902709 in hypocretin neuropeptide precursor (HCRT) and OSAHS in Chinese Han individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, gene association studies also reveal a significant relationship between the genetic predisposition for narcolepsy-cataplexy and OSA. Specifically, a distinct polymorphism of the preproorexin gene has been associated with OSA (5, 89). It is possible that subtle metabolic consequences of orexin deficiency contribute to the link between OSA and narcolepsy.…”
Section: Neural Control Of the Upper Airway In Sleep-disordered Breatmentioning
confidence: 99%